Prediksi Harga Rumah Berbasis Machine Learning dengan Explainable AI untuk Interpretabilitas Faktor Penentu - Hadijah; Wiwin Handoko; Rizty Maulida Badri (Management of Information System Journal, 2026)
House prices are determined by numerous interrelated factors, making it essential to develop prediction methods that are not only accurate but also interpretable by property business practitioners, investors, and policymakers. This study aims to construct a house price prediction model using a machine learning approach integrated with Explainable Artificial Intelligence (XAI) to produce predictions that are more transparent and comprehensibly interpretable. The data used in this study were derived from real property listings, incorporating several key variables including building area, land area, number of bedrooms, number of bathrooms, and garage capacity. Four machine learning algorithms were evaluated and compared, namely Linear Regression, Random Forest, XGBoost, and Gradient Boosting. The performance of each model was assessed using multiple evaluation metrics, comprising Mean Absolute Error (MAE), Root Mean Squared Error (RMSE), coefficient of determination (R²), and Mean Absolute Percentage Error (MAPE). Experimental results demonstrate that the Random Forest algorithm achieved the best performance, yielding an R² value of 0.7636, MAE of IDR 1.305 billion, RMSE of IDR 2.037 billion, and MAPE of 25.84%. The best-performing model was subsequently analyzed using SHapley Additive exPlanations (SHAP) to provide both global and local model interpretability, as well as Local Interpretable Model-agnostic Explanations (LIME) to explain individual predictions at the instance level. The analysis reveals that building area and land area are the most influential factors in determining house prices. The proposed approach demonstrates a measurable improvement in model transparency, rendering prediction outcomes more comprehensible and trustworthy for end users.